1995
DOI: 10.1177/014920639502100506
|View full text |Cite
|
Sign up to set email alerts
|

Rationality in Strategic Decision Processes, Environmental Dynamism and Firm Performance

Abstract: This study tests competing theories of how the relationship between rationality in strategic decision processes and firm performance may be moderated by environmental dynamism. Results, based on a survey of 101 manufacturing firms, indicate a positive rationality-performance relationship for firms facing dynamic environments, but no relationship between rationality and performance for firms facing stable environments. Implications for future research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
1
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(89 citation statements)
references
References 52 publications
3
84
1
1
Order By: Relevance
“…Environmental dynamism has been also investigated on the relationship between insider ownership and firms' performance (Li and Simerly, 1998). It also had a moderating effect on the relationship between managers' rationality and firm's performance (Priem et al, 1995). In the supply chain and operations management literatures, dynamism, the degree of changes in product design, technology, and customer preferences has been viewed as relationship perspective between supply chain networks.…”
Section: H1-3: Munificence Positively Affects Integration With Custommentioning
confidence: 99%
“…Environmental dynamism has been also investigated on the relationship between insider ownership and firms' performance (Li and Simerly, 1998). It also had a moderating effect on the relationship between managers' rationality and firm's performance (Priem et al, 1995). In the supply chain and operations management literatures, dynamism, the degree of changes in product design, technology, and customer preferences has been viewed as relationship perspective between supply chain networks.…”
Section: H1-3: Munificence Positively Affects Integration With Custommentioning
confidence: 99%
“…The literature provides strong support for the technique of subjective performance measurement (e.g. Dess and Robinson, 1984;Pearce et al, 1987;Priem et al, 1995;Brews and Hunt, 1999). The measurement scales that we used in this study are shown in the Appendix.…”
Section: Execution Of the Surveymentioning
confidence: 99%
“…Yet, as we shall show below, the existence of universal cognitive biases in all humans and in all leaders and managers -and yes, risk analysts -means that much decision-making is fundamentally flawed (Richard L. Priem, 1995). This has not been addressed at all in the classical risk canon.…”
Section: Ignores Decision-making Biasesmentioning
confidence: 99%